Obraz kapłana-duszpasterza w nauczaniu św. Grzegorza z Nazjanzu - Wygralak, Paweł (Vox Patrum, 2015)
The article presents the thoughts of St. Gregory of Nazianzus on the attitudes of priests in their pastoral work. The bases of this study are selected speeches and works of poetry by St. Gregory. The Bishop of Nazianzus indicates first and foremost the importance of the spiritual formation of each priest. Without reducing the importance of an intellectual formation, he puts the concern for the development of the inner life in the primary place. The deeply spiritual priest, having a thorough theological knowledge, can take up the mission of proclaiming God’s word responsibly. The fruitfulness of this ministry also depends on the discernment of the spiritual, moral and intellectual state of the faithful, whom he is serving. St. Gregory also points out the dangers that threaten every priest. These are above all: pride, which leads to the desire to rule and not to serve, as well as materialism and the use of one’s office to further one’s own private interests.